Uji kinerja mesin bensin 110 cc sistem injeksi mekanis berbahan bakar gas LPG - Marthen Paloboran; Haruna; Syafiuddin Parenrengi; Faizal Amir; Asrul (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
This research is experimental research using a 110 cc petrol engine with a chassis type dyno test measuring instrument. This research aims to determine the performance and exhaust emissions when using LPG and pertalite gas. The engine speed variation in this research is 2500-5000 rpm. Data collection techniques use observation techniques to record the test results obtained. The data analysis technique uses descriptive analysis to present research results. As for the research results from the engine performance analysis, it was found that there was an increase in engine performance at each engine rotation, the lowest power was obtained when using LPG gas fuel at 2500 rpm of 2.22 kW and pertalite fuel of 2.73 kW. Meanwhile, the highest power was obtained when using LPG gas fuel at 5000 rpm of 4.88 kW and using pertalite fuel of 4.81 kW. However, for fuel consumption, the lowest consumption was obtained when using LPG gas. Meanwhile, for exhaust gas emission analysis, it was found that there was a decrease in emission levels when using LPG gas. It was found that CO and HC exhaust emissions increased as the engine speed increased, so emissions decreased further. However, CO2 gas emissions increase with each engine rotation compared to using LPG gas.